The Concept of Profit In Syirkah Al-‘Inān Islamic Economic Perspective: Study at People's Banks Ipoh, Perak Malaysia - Junaidy, Athailah; Ikbal, Muhammad; Zulhamdi, Zulhamdi (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2023)
This research is about studying the concept of